Refined cassava flour in bread making: a review (2017)
Different studies have developed a variety of breads using cassava flour, with similar characteristics to wheat flour breads. The use of cassava flour in bread making is a convenient alternative for promoting the use of a local crop as well as reducing imports of wheat flour, promoting the production of high quality cassava flour, offering a gluten-free product and developing biofortified and fortified foods. Although the substitution level of cassava flour is limited, in some products, the incorporation of additives or flours from other crops improve the nutritional value and breadmaking quality of the baked foods. Several limitations have hindered the success of initiatives to promote, in some cassava producing countries, the intensive use cassava flour in bread making. Among these include the costs and efficiency of processing technologies, standards of the quality of cassava flour and lack of favorable policies. Further studies about bioavailability and retention of nutrients on baked foods and evaluation on the effects of processing cassava flour in relation to increasing the resistance starch are required to provide scientific evident for the health benefits of this flour.